Tri- and hexaferrocenyl-substituted subphthalocyanines in the quest for the optimum electron donor-acceptor distances - Fernandez-Ariza, Javier; Krick Calderon, Rafael; Perles, Josefina; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemical Communications, 2017)
Three and six ferrocenyl subunits have been attached to the periphery of subphthalocyanines (SubPcs). Unlike axially coordinated ferrocenes, peripherally-bonded ferrocenes have an impact on the electronic features of SubPcs, which show a 44 to 70 nm red-shift of their Q-bands. The unusually deep and narrow ferrocenyl-SubPc is able to host C60, giving rise to atypical SubPc•C60 cocrystallates, through a combination of concave-convex and convex-convex π-π interactions.
CRIS-Team Scopus Importer:2022-04-14